GJG-31: A high yielding and better quality Spanish bunch type groundnut (Arachis hypogaea L.) variety for Gujarat state: GJG-31: A HIGH YIELDING BETTER QUALITY SPANISH BUNCH TYPE GROUNDNUT VARIETY - J H VACHHANI,; K L DOBARIYA,; L L JIVANI,; V H KACHHADIA,; H G SHEKHAT, (Journal of Oilseeds Research, 2014)
A Spanish bunch type groundnut genotype GJG-31 is a hybrid derivative of the cross GG-2 x PBS-21065. It has recorded an overall mean pod yield of 3483 kg/ha, which was higher than the check varieties viz., GG-2 (2545 kg/ha), GG-4 (2812 kg/ha), GG-6 (2965 kg/ha) and TG-26 (2887 kg/ha). Thus, this genotype expressed an overall improvement of 36.86 per cent, 24.07 per cent, 17.47 per cent and 20.64 per cent in pod yield over the check varieties GG-2, GG-4, GG-6 and TG-26, respectively. This genotype was also tested in trials of All India Coordinated Research Project i.e. Initial Varietal Trial-Spanish Bunch-I and II during summer seasons of 2008 and 2009, respectively, where the performance was better than the local check variety GG-6 (14.46%) and zonal check variety TG-26 (11.79%). However, it was comparable with check varieties viz., TAG-24, TG-37A and Dh-86. The kernel yield (2460 kg/ha) of GJG-31 was also higher than the check varieties viz., GG-2 (1822 kg/ha), GG-4 (2115 kg/ha), GG-6 (2174 kg/ha) and TG-26 (2159 kg/ha). GJG-31 recorded average 100-kernel weight of 40.77 g, average 100-pod weight of 115.3 g and average shelling out-turn of 70.62 per cent. GJG-31 was found free from peanut bud necrosis disease incidence as disease was not appeared in this variety. Due to its consistent superior performance, GJG-31 has been released for general cultivation in the summer bunch groundnut growing areas of Gujarat state.